What To Knit : The Toddler Years : 30 gorgeous jumpers, cardigans, hats, toys & more - Van De Car, Nikki (Kyle Books, 2014)
Toddlers and young children are energetic, curious, enthusiastic - and messy! The 30 patterns in What to Knit: The Toddler Years reflect this, allowing you to show their individuality whilst emphasising practicality and comfort, with advice on machine washable yarns.